GABARAP activates ULK1 and traffics from the centrosome dependent on Golgi partners WAC and GOLGA2/GM130 - Joachim, Justin (Autophagy, 2016)
WAC and GOLGA2/GM130 are 2 Golgi proteins that affect autophagy; however, their mechanism of action was unknown. We have shown that WAC binding to GOLGA2 at the Golgi displaces GABARAP from GOLGA2 to allow the maintenance of a nonlipidated centrosomal GABARAP pool. Centrosomal GABARAP can traffic to autophagic structures during starvation. In addition GABARAP specifically promotes ULK1 activation and this is independent of GABARAP lipidation but likely requires a LIR-mediated GABARAP-ULK1 interaction.